Detection of atypical porcine pestivirus in Brazil in the central nervous system of suckling piglets with congenital tremor - Gatto, I. R.H. [UNESP]; Harmon, K.; Bradner, L.; Silva, P. [UNESP]; Linhares, D. C.L.; Arruda, P. H.; de Oliveira, L. G. [UNESP]; Arruda, B. L. (Hindawi, 2018)
Atypical porcine pestivirus (APPV) has been detected in piglets with congenital tremor (CT) from three different continents including North America, Europe and Asia. Thirteen piglets from four farms in two different states in Brazil with CT were sampled. Viral RNA was detected by quantitative real-time PCR in the cerebellum or cerebellum and spinal cord in the 100% of the piglets with CT, and APPV was not detected in any tissue sample from clinically non-affected piglets with the exception of the cerebellum of one piglet from Farm A. Piglets with CT had an odds ratio of 99.0 (95% CI 3.4, 2823.8; p =.0072) compared to piglets without CT to test positive for APPV by qRT-PCR. A subset of positive samples was selected for sequencing of the NS3 gene. Phylogenetic analysis revealed that Brazilian sequences of the NS3 formed an independent cluster and had the highest sequence identity with a sequence from the United States. This is the first identification of APPV infection in piglets with CT in South America.
Keywords: atypical porcine pestivirus; Brazil; congenital tremor